Efficient sampling of ground-dwelling arthropods using pitfall traps in arid steppes - Cheli, German Horacio (2010)
Pitfall trapping is probably the most frequently used method for sampling grounddwelling arthropods. While the capture of specimens in pitfall traps largely depends on the number of individuals in the sampled area, trap design and trapping effort for a given environment, can also affect sampling success. The aim of this study was to determine the best pitfall trapping design for collecting ground-dwelling arthropods in the wind-blown and cold arid steppe areas of Patagonia. We tested four designs of traps, six types of preservative and different times of activation as well as the quantity of traps. Both preservation attributes and sampling effi ciency differed between different trap designs and fl uids compared. We conclude that in order to obtain reliable data on the structure of a community of ground-dwelling arthropods in Patagonia, at least three pitfall traps per experimental unit are required. In addition, traps should be opened for a minimum of 10 days fi lled with 300 ml of 30% ethylene glycol. We also suggested the use of a simple trap design (i.e. without funnel or roof). We believe these fi ndings will contribute to more appropriate sampling of the ground dwelling fauna of Patagonia as well as other arid areas, leading to more reliable diversity studies.